Exploring the cultural significance of sculpture in urban public spaces - Longcheng Cui; Musnin Bin Misdih (Human Resource Management Academic Research Society, 2025)
This paper discusses the cultural significance of sculpture in urban public spaces and its impact on urban image, local identity, and social interaction. As a distinctive art form, sculpture not only enhances the aesthetic appeal of urban environments but also serves as a cultural bridge between history and the future, fostering emotional resonance among citizens and strengthening community identity. Through interviews, this paper provides insights into the perceptions and views of local residents, artists and cultural scholars, tourists and visitor groups, and community managers on the cultural significance of urban public sculpture. This study argues that sculpture fulfills multiple functions in urban public spaces, including environmental beautification, historical commemoration, social value expression, and participation in the creation of urban public art. Moreover, through its visual and symbolic nature, sculpture can provide emotional support for urban residents, offering a sense of cultural belonging and spiritual connection. To fully realize these cultural functions, the design and placement of sculptures should align with community needs, cultural contexts, and social values. Additionally, the integration of digital technology presents new opportunities for innovation in urban sculpture. This paper highlights that through government policy support, public engagement, and technological advancements, sculpture can play a vital role in urban cultural development, infusing public spaces with renewed vitality. As a key medium of urban culture, sculpture not only enhances the urban landscape but also serves as a vehicle for historical transmission and spiritual expression. Future research should further explore how to optimize spatial planning and technological applications in sculpture to accommodate the evolving cultural demands of urban societies.